PET/CT versus bone marrow biopsy in the initial evaluation of bone marrow infiltration in various pediatric malignancies. Issue 2 (13th September 2017) - Zapata, Claudia P.; Cuglievan, Branko; Zapata, Catalina M.; Olavarrieta, Raquel; Raskin, Scott; Desai, Kavita; De Angulo, Guillermo
Abstract: Accurate staging is essential in the prognosis and management of pediatric malignancies. Current protocols require screening for marrow infiltration with bone marrow biopsy (BMB) as the gold standard. Positron emission tomography–computed tomography (PET–CT) is commonly used to complete the staging process and can also be used to evaluate marrow infiltration. Objective: To compare PET–CT and BMB in the initial evaluation of bone marrow infiltration in pediatric cancers. Design/method: We retrospectively reviewed new cases of EWS, rhabdomyosarcoma, neuroblastoma, and lymphoma diagnosed between January 2009 and October 2014. Each case had undergone both PET–CT and BMB within 4 weeks without treatment in the interval between screening modalities. Results: We reviewed 69 cases. Bone marrow infiltration was demonstrated in 34 cases by PET–CT and in 18 cases by BMB. The sensitivity and negative predictive value of PET–CT were both 100%. Interestingly, the cases in which infiltration was not detected on BMB had an abnormal marrow signal on PET–CT focal or distant to iliac crest. Conclusion: PET–CT has a high sensitivity when assessing marrow infiltration in pediatric malignancies. Advances in radiologic modalities may obviate the use of invasive, painful, and costly procedures like BMB. Furthermore, biopsy results are limited by insufficient tissue or the degree of marrow infiltration (diffuse vs. focal disease). PET–CT can improve the precision of biopsy when used as a guiding tool. This study proposes the use of PET–CT as first‐line screening for bone marrow infiltration to improve the accuracy of staging in new diagnoses.